1996
DOI: 10.1177/026988119601000303
|View full text |Cite
|
Sign up to set email alerts
|

Systemic idazoxan impairs performance in a non-reversal shift test: implications for the role of the central noradrenergic systems in selective attention

Abstract: Two experiments examined the effect of pharmacological stimulation of the locus coeruleus in a non-reversal shift paradigm to test predictions concerning the role of the ceruleo-cortical noradrenergic system in processes of selective attention. Food-deprived rats were trained to make either visual (experiment 1) or spatial (experiment 2) discriminations in a parallel alley with both sets of cues being present at all times. Two groups of rats received treatments of either 2 mg/kg i.p. of the selective α(2) adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
2
6
2
1
Order By: Relevance
“…Thus, although presynaptic modulation of NA function with the low doses of clonidine used in the current study had little effect on the efficiency of attentional shifting compared to spatial memory (Coull et al 1995a), more profound disruption of the NA system through the additional effects of an α 2 antagonist reveals that NA does have a role in the redirection of an attentional set towards newly relevant environmental stimuli. Such evidence is consistent with reports of narrowed attentional focus in rats during the acquisition of non-reversal shifts following administration of idazoxan (Rowe et al 1996).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, although presynaptic modulation of NA function with the low doses of clonidine used in the current study had little effect on the efficiency of attentional shifting compared to spatial memory (Coull et al 1995a), more profound disruption of the NA system through the additional effects of an α 2 antagonist reveals that NA does have a role in the redirection of an attentional set towards newly relevant environmental stimuli. Such evidence is consistent with reports of narrowed attentional focus in rats during the acquisition of non-reversal shifts following administration of idazoxan (Rowe et al 1996).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the levels of NE that are released during alert, non-stressed periods optimize prefrontal cognitive functioning by engaging α2A-receptors (Arnsten & Goldman-Rakic, 1985), whereas the high levels of NE that are released in response to a stressor impair PFC-related cognitive processes by stimulating lower-affinity α1-receptors and β1-receptors (Birnbaum et al, 1999;Ramos et al, 2005). In line with these findings, blockade of α1 receptors in rats improved set-shifting, whereas chronic α2 receptor antagonism had the opposite effect (Rowe et al, 1996). Likewise, it has been reported that intra-medial PFC infusions of a postsynaptic α1 receptor antagonist prevented the attentional set-shifting improvement observed following systemic injections of an adrenergic auto-receptor antagonist (atipamezole) in rats (Lapiz and Morilak, 2006).…”
Section: Norepinephrinesupporting
confidence: 54%
“…Other early studies of effects of DNAB lesions on ED‐shifting in rats in a paradigm utilizing shifts between spatial and visual cues were confounded by deficits in acquisition (Mason & Lin, 1980). The effects of systemic manipulations of drugs such as the NA adrenoceptor‐2 antagonist idazoxan on similar spatial to visual shifts (Devauges & Sara, 1990) were not confirmed when a fully counterbalanced design was employed (Rowe et al ., 1996). However, recent findings of a role for postsynaptic α‐2 receptors in the mPFC in the ED‐shift are fully consistent with the findings of the present study (Lapiz & Morilak, 2006).…”
Section: Discussionmentioning
confidence: 99%